Early Buddhist metaphysics : the making of a philosophical tradition - Ronkin, Noa, 1973- (RoutledgeCurzon, 2005)
Early Buddhist Metaphysics provides a philosophical account of the major doctrinal shift in the history of early Theravada tradition in India: the transition from the earliest stratum of Buddhist thought to the systematic and allegedly scholastic philosophy of the Pali Abhidhamma movement. Entwining comparative philosophy and Buddhology, the author probes the Abhidhamma's metaphysical transition in terms of the Aristotelian tradition and vis-à-vis modern philosophy, exploits Western philosophical literature from Plato to contemporary texts in the fields of philosophy of mind and cultu.